2021
DOI: 10.30939/ijastech..796769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intake Valve Lift Form Modulation on Exhaust Temperature and Fuel Economy of a Low-loaded Automotive Diesel Engine

Abstract: Exhaust after-treatment (EAT) systems on automotive vehicles cannot perform effectively at low loads due to low exhaust temperatures (Texhaust < 250 o C). Conventional late intake valve closure (LIVC) technique -a proven method to improve diesel exhaust temperatures -generally requires the modulation of the whole valve lift profile. However, an alternative method -boot-shaped LIVC -only needs partial lift form modulation and can rise exhaust temperatures significantly. Therefore, this study attempts to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous works demonstrated that the implementation of single-VVT has a definite potential on EAT warmup. However, singlevalve modulations increase only the exhaust temperature without considering mass flow rate at the EAT inlet and, therefore, decelerate after-treatment warmup [44] or need a dramatic fuel consumption penalty for a moderate improvement in EAT warmup [45]. The implementation of combined VVT techniques can be a solution for fast EAT warmup without suffering an extreme fuel consumption penalty at low loads.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works demonstrated that the implementation of single-VVT has a definite potential on EAT warmup. However, singlevalve modulations increase only the exhaust temperature without considering mass flow rate at the EAT inlet and, therefore, decelerate after-treatment warmup [44] or need a dramatic fuel consumption penalty for a moderate improvement in EAT warmup [45]. The implementation of combined VVT techniques can be a solution for fast EAT warmup without suffering an extreme fuel consumption penalty at low loads.…”
Section: Introductionmentioning
confidence: 99%